THE INFLUENCE OF WORK-LIFE BALANCE, ADAPTIVE PERFORMANCE, AND PERCEIVED ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE AT CV. SS JAYA GRUP: Pengaruh Work-Life Balance, Kinerja Adaptif, dan Persepsi Dukungan Organisasi terhadap Kinerja Karyawan pada CV. SS JAYA GRUP - Muhammad Fathurizam; Heru Sutapa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Employee performance is one of the important factors in supporting the achievement of organizational goals and is influenced by individual conditions and work environment support. This study aims to analyze the influence of work-life balance, adaptive performance, and perceived organizational support on employee performance on CV. SS JAYA GRUP as a medium-scale company. The research uses a quantitative approach with an explanatory research design. The entire population of 40 employees was sampled through saturated sampling techniques. Data collection was carried out using a four-point Likert scale questionnaire, then analyzed through validity, reliability, classical assumption test, simple regression, and multiple linear regression. The results showed that work-life balance, adaptive performance, and perceived organizational support partially and simultaneously had a positive and significant effect on employee performance, with a determination coefficient of 72.9%. Among these variables, Work-Life Balance had the most substantial effect on employee performance. This research provides empirical insights into the relationship between individual and organizational factors in shaping employee performance in medium-sized companies.